Avoiding the Coming Tsunami of Common, Chronic Disease: What the Lessons of the COVID-19 Pandemic Can Teach Us. Issue 19 (11th May 2021) - Califf, Robert M.
Abstract : During the past year, clinicians and the public have been focused on the coronavirus disease 2019 (COVID-19) pandemic and its associated societal and economic effects. However, once the acute phase of this crisis has passed, we will face an enormous wave of death and disability as a result of common chronic diseases (CCDs), with cardiometabolic diseases at the crest (Figure). A tsunami results when an earthquake on the ocean floor creates huge waves that can wreak devastation far distant from the original upheaval, especially when warnings are ignored. Similarly, underlying global and national demographic and risk factor profiles have for some time presaged an overwhelming burden of CCDs. However, although the pandemic has created additional impetus that unless heeded will amplify the consequences of this burden, the rapid adaptations and innovations in care and research prompted by the urgent response to it may also offer us the means to stem this flood.